Nursing process addressing the focus “anxiety”: a scoping review - Sampaio, Francisco (2021)
The aim of this review was to map the body of literature on data, diagnoses and interventions addressing the nursing focus “anxiety.” A scoping review methodology was employed. The Joanna Briggs guidelines for scoping reviews and PRISMA checklist for scoping reviews were followed. Electronic database searches (MEDLINE, CINAHL and Web of Science) located 829 articles. From the total of articles located, 165 were included. The nursing diagnosis “anxiety” can be considered a parent diagnosis, from which other children diagnoses are derived. Data that lead to nursing diagnoses in the anxiety domain can be divided into cognitive and somatic data. Some interventions, such as educational and music-based interventions, seem to be useful to address nursing diagnoses in the anxiety domain. The findings of this review can add substantial value for systematising the nursing process related to the focus “anxiety.” Therefore, reaching consensus regarding this nursing process seems highly relevant.